Morphological, thermal, rheological, and mechanical properties of PP/EVOH blends compatibilized with PP‐g‐IA. Issue 11 (24th May 2016) - Kim, Jung Soo; Jang, Ji Hoon; Kim, Jin Hoon; Lim, Dae Young; Lee, Youn Suk; Chang, Young‐Wook; Kim, Dong Hyun
Abstract : We prepared some blends of polypropylene (PP) and ethylene vinyl alcohol (EVOH) with and without a compatibilizer. As a new compatibilizer, we synthesized polypropylene grafted with itaconic acid (PP‐ g ‐IA) using Brabender mixing system. We investigated the morphological, thermal, rheological, and mechanical properties of a compatibilized blends (PP/EVOH/PP‐ g ‐IA) and not compatibilized blends (PP/EVOH). Our experiments showed that carboxylic acid groups in PP‐ g ‐IA and hydroxyl group in EVOH formed strong in situ hydrogen bond in the compatibilized blends, resulting in better morphological and mechanical properties of the compatibilized blends than those of not compatibilized blends. POLYM. ENG. SCI., 56:1240–1247, 2016. © 2016 Society of Plastics Engineers